Immediate and delayed loading of two-piece reduced-diameter implants with locator-analog attachments in edentulous mandibles: one-year results from a randomized clinical trial examining clinical outcome and patient expectation - Giannakopoulos, Nikolaos Nikitas; Eberhard, Lydia; Klotz, Anna-Luisa; Oh, Keunyoung; Kappel, Stefanie (Clinical implant dentistry and related research, 2017)
Background Prosthetic management of thin alveolar ridges in the edentulous mandibles of elderly patients, especially the time of loading, the number of implants needed, and patient expectations and perception, is a challenge in implant dentistry. Purpose Survival of conventionally and immediately loaded 2-piece reduced-diameter implants in the interforaminal region of the edentulous mandible supporting locator-analog attachments was evaluated. Prosthetic complications and peri-implant hygiene were also studied, and patient expectation and subjective evaluation of the treatment were documented. Material and Methods Twenty-five patients with adapted complete dentures received 4 reduced-diameter implants. All anterior implants were immediately loaded. Three months later, patients were allocated by randomization to 1 of 2 treatment groups: 2 locator-analog attachments on the anterior implants (Group A); or 4 locator-analog attachments (Group B). After another 3 months patient allocation was changed (crossover design) for the next 3 months. Questionnaires with Likert scales and numeric rating scales were used to assess patients' expectations and subjective overdenture-related variables, respectively. Results One implant was lost in the immediate-loading group. Survival was 98% and 100% for immediate and delayed loading, respectively. During 12-month observation, 8 complications required aftercare. At the beginning of treatment, patients' expectations were highly positive. Subjective assessment of overdenture-related variables 3 months after immediate loading of 2 implants revealed a statistically significant improvement for most of the variables studied; this was maintained 1 year later. In the subjective assessments, there were no statistically significant differences between Groups A and B. Conclusion Immediate loading of reduced-diameter implants supporting locator-analog attachments resulted in high implant survival, few prosthetic complications, good oral hygiene, and improvement of subjective denture perception in the short-term. It might be a promising treatment option, especially for elderly patients with a narrow mandibular ridge.
Gesehen am 08.06.2018